Study of Teakwood Quality from Community Forests in Gunungkidul. VI. Inorganic Material Contents and Acidity - Ganis Lukmandaru; Rudy Nur Hidayah (Jurnal Ilmu Kehutanan)
Inorganic materials and acidity in the wood has been proved to affect the wood properties. The previous paper in this series reported on the physical and chemical properties of teak wood from community forests. Therefore, this study aimed to explore the content of inorganic materials and acidity of teak wood grown in the 3 sites (Panggang, Playen, Nglipar) with different ecological attributes from community forests in Gunungkidul. The evaluated parameters were pH values, the contents of ash (ASTM D-1102), silica and silicates (SNI 14-1031-1989), and inorganic matters (Ca, Mg, K, Na, Fe, Mn, and Cu) by means of Atomic Absorption Spectrophotometer. The ranges of ash and silica-silicates content were 0.38-2.62%, and 0.01-1.17%, respectively. The ranges of inorganic element content for Ca, K, Mg, Na, and Fe were 408–2919 ppm; 69 – 23705 ppm; 947–1653 ppm; 4 – 31 ppm; and 0 – 326 ppm, respectively whereas Mn and Cu were not detected in any samples. Further, the obtained pH values range was 5.23–6.98. On the basis of analysis of variance, the contents of ash, silica-silicates, and Na were affected significantly by site and radial direction (sapwood, outer heartwood, and inner heartwood) factors. The woods from Playen (middle zone/Ledok Wonosari) had significantly high in ash and silica-silicate contents. By Kruskal-Wallis test, radial direction factor affected significantly the levels of Ca, K, and Mg. As defined by Pearson’s correlation analysis, it was found a strong correlation between the ash and silica-silicates contents (r=0.77-0.88), as well as between the ash-Ca content (r=-0.51) and the ash-Mg content (r=0.59) in the heartwood part. In the inorganic element levels, the strongest correlation was measured between Ca-Mg content (r=-0.46). Special attention should be given to the comparatively high amounts of the silica-silicates content in the observed samples as it would dull cutting tools considerably.